The Penanaman Karakter Cinta Lingkungan pada Peserta Didik melalui Program Mini Garden - Elsafira, Defi Amalia; Jannah, Ana Naimatul (Edu Berkah Khatulistiwa, 2024)
This research aims to analyze the cultivation of the character of love for the environment in students at SD Negeri Mlajah 2 Bangkalan through the